AGRICULTURAL LAND CONVERSION: DETERMINANTS AND IMPACT FOR FOOD SUFFICIENCY IN SLEMAN REGENCY - Rika Harini; Hadi Sabari Yunus; Kasto .; Slamet Hartono (Faculty of Geography, Universitas Gadjah Mada, 2012)
The research was conducted in Sleman Regency with 3 study area based on the extent ofagricultural land conversion. The purpose of this research is to examine the determinants ofagricultural conversion internally and externally, as well as the impact on the availability offood, especially rice. The research was conducted by survey method and statistical analysisregression Ordinary Least Square. The resultsof this research showed that the internalfactors which significantly affect land conversion is the price of land and land location in allareas of study. External factors have significantly positive are variable population, landconversion rules and land location, while the variable GDP in the agricultural sectornegatively. Availability of rice in Sleman Regenct zone 1 indicates the region from 1983 to2025 for the population minus the rice sufficiency. In zone 2 region between 1983 and 2005but it is still a surplus between 2006 and 2025 minus. In the area of zone 3 is projectedthrough 2025 the availability of rice is sufficient